The Effect of Advanced Access Implementation on Quality of Diabetes Care - Sperl-Hillen, JoAnn M (Centers for Disease Control and Prevention, 2007)
INTRODUCTION: The study analyzes the effect of an advanced access program on quality of diabetes care. METHODS: We conducted this study in a medical group of 240,000 members served by 17 primary care clinics. Seven thousand adult patients older than 18 years of age with diabetes were identified from administrative databases. Two aspects of advanced access — wait time for appointments and continuity of care — were calculated yearly for each patient during 1999 through 2001. We developed three composite measures of glucose and lipid control — process (proportion of patients with appropriate testing rates of hemoglobin A1c [HbA1c] and low-density lipoprotein [LDL]), good control (proportion with HbA1c < 8% and LDL < 130 mg/dL) and excellent control (proportion with HbA1c < 7% and LDL < 100 mg/dL) — and assessed them each year for each patient. We used multilevel logistic regression to predict the measures in 2000 and 2001 (years during and after advanced access implementation) relative to 1999 (year pre-advanced access). RESULTS: After implementation of advanced access, wait time decreased from 21.6 days to 4.2 days, and continuity improved by 6.5% (both P <.01). The percentage of patients with HbA1c < 7% increased from 44.4% to 52.3% and with LDL < 100 mg/dL from 29.8% to 38.7%. Increased continuity predicted improved process (P = .01), good control (P = .033), and excellent control (P <.001). However, wait time did not significantly predict process (P = .62) or quality measures (P = .95). CONCLUSION: Measures of the quality of diabetes control improved in the year after implementation of advanced access, but better care did not correlate with decreased wait time to see a provider. However, improved continuity of care predicted improvements in both process and quality of diabetes care.